Research progress on the treatment and nursing of sensorineural hearing loss - Liu, Fangfang; Han, Baoai; Zhou, Xuhong; Huang, Shuo; Huang, Jing (Frontiers in Neuroscience, 2023)
This article provides a comprehensive review of the progress in the treatment and care of sensorineural hearing loss (SNHL), which is a common disease in the field of otolaryngology. In recent years, the incidence of SNHL has been on the rise due to factors such as fast-paced lifestyles, work pressure, and environmental noise pollution, which have a significant impact on the quality of life of patients. Therefore, the study of the treatment and care of SNHL remains a hot topic in the medical community. Despite significant advances in this field, there are still some challenges and limitations. For example, there is currently no single method that can completely cure SNHL, and the effectiveness of treatment may vary significantly among individuals. In addition, due to the complex etiology of SNHL, the prognosis of patients may vary greatly, requiring the development of personalized treatment plans and care strategies. To address these challenges, continuous research is needed to explore new treatment methods and care models to improve the quality of life of patients. In addition, there is a need for health education programs for the general public to raise awareness of SNHL and promote preventive measures to reduce its incidence. The ultimate goal is to ensure the sustainable development of the field of SNHL treatment and care, thus ensuring the health and well-being of affected individuals.